Age and perceived stress as correlates to life satisfaction among medical students from Medical Schools in Manila - Loria, Danice D. 4 0 16; 5 (2019)
ABSTRACT: Rate of the satisfaction in life of students is most likely questionable. The rationale for this study was to find out how the age and stress levels among medical students affect their life satisfaction. The study was accomnplished to 100 medical students in Taft, Manila. The used of the Perceived Stress Scale and Satisfaction with Life Scale as an instrumnents to seek the answer to the problem: is there a significant relationship with age and perceived stress towards satisfaction with life; identify the numbers of medical students in perceived stress and satisfactory in life. The study was able to answer the questions that resulted to: (a) most of the medical student were moderately stressed and satisfied with their lives. (b) Perceived stress rejected that there is no significant relationship with life satisfaction. (c) Age accepted that there is no significant relationship with perceived stress, (d) Age has no significant relationship with life satisfaction among medical students from medical schools in Manila.
Undergraduate Thesis: (B.S. Psychology)-Pamantasan ng Lungsod ng Maynila, 2019.
Keywords: 2 -- 0; 6; 20; 20; 2